Radical Hydrodehalogenation of Aryl Bromides and Chlorides with Sodium Hydride and 1,4‐Dioxane - Hokamp, Tobias (Angew Chem Int Ed Engl, 2017)
A practical method for radical chain reduction of various aryl bromides and chlorides is introduced. The thermal process uses NaH and 1,4‐dioxane as reagents and 1,10‐phenanthroline as an initiator. Hydrodehalogenation can be combined with typical cyclization reactions, proving the nature of the radical mechanism. These chain reactions proceed by electron catalysis. DFT calculations and mechanistic studies support the suggested mechanism.